The making of design : from the first model to the final product - Terstiege, Gerrit, ....- (Basel : Birkhäuser, 2009)
This book takes an in-depth look at design processes, with 25 depictions of "the making of" products from a wide variety of industries. Renowned designers like Konstantin Grcic, the Bouroullecs, or Hella Jongerius show how they go about designing products, the tools they use for visualization and how projects change during the model phase.